Enhancing Project Management Governance in Digital Transformation: A Case Study on Deploying Simplified Togaf Artifacts - Budianto, Farhan Alif; Lubis, Muharman; Mukti, Iqbal Yulizar; Budianto, Setyo (Jurnal Locus Penelitian dan Pengabdian, 2025)
Digital Transformation (DT) acceleration requires robust project management governance that tightly integrates Enterprise Architecture (EA) with agile project delivery. Although The Open Group Architecture Framework (TOGAF 10) is the leading EA standard, its complexity hinders adoption, especially for resource-limited organizations. This study tackles this challenge by proposing and validating a simplified TOGAF 10 framework called "Mini TOGAF." The goal is to improve EA implementation, streamline project management, and enhance strategic alignment. Using a Design Science Research (DSR) approach, a case study at PT Nuon Digital Indonesia—an established digital content and entertainment firm—was conducted. The research involved a systematic literature review to identify essential TOGAF artifacts, followed by iterative development and stakeholder validation of the Mini TOGAF blueprint across Business, Data, Application, and Technology layers. The model consolidates artifacts, merging Terms of Reference and Architecture Principles into unified Architecture Guidelines, and focuses implementation on short- to medium-term objectives. Implementation led to significant gains in operational efficiency via process optimization, increased business agility, and better alignment of IT investments with corporate goals. This paper contributes a validated Mini TOGAF blueprint that bridges the gap between TOGAF’s comprehensive rigor and the practical demands of agility and efficiency in digital transformation. The model offers a resource-efficient, scalable procedural guide for organizations—especially those facing resource constraints—to harness EA for effective project management governance without overwhelming complexity.